ChemInform Abstract: Magnetic Solid Phase Extraction Applied to Food Analysis. Issue 8 (February 2016) - Ibarra, Israel S.; Rodriguez, Jose A.; Galan‐Vidal, Carlos A.; Cepeda, Alberto; Miranda, Jose M.
Abstract: Review: 75 refs.